Hubungan Beberapa Sifat Fisik Terhadap Kemantapan Agregat Ultisol Akibat Pemberian Campuran Pupuk Kandang Kotoran Sapi Dan Tithonia Defersifolia Pada Tanaman Kacang Kedelai - Hasriati Nasution; Asmadi Saad; Sri Mulyati (Riviera Publishing, 2025)
The purpose of the study is to determine the optimal dosage of n mixture of cow manure and Thitonia Defprsofolia for soybean plants. The usefulness of the results of the research will be to make a recommendation of the fertilizer of cow manure, drum manure, and Tithonia Defersofolia to the stability of the aggregate and some physical properties of the soil so that the soil can be used sustainably. The research was conducted experimentally with the treatment of applying manure to cow manure and Tithodia Deserfifolia. By using the Group Design (RAK) with 6 treatments and 4 repeats so that there are 24 experimental plots with a plot size of 2 x 3 m. The observed parameters are percent aggregate, aggregate stability and C- organic concentration. Volume Weight, Total Pory Space, Moisture Content and Yield of Soybean Plant. The data analyzed were the aggregate percent and aggregate stability, organic - C content, soil volume weight, total pore space,, percent aggregate and stability of aggregate and soybean yield in the test using the Group Random Design and followed by the Duncan Distance Test at the level of 5% and to find the relationship between physical properties and aggregate stability using Linear Regression and Multiple Linear Regression. From the results of the research on the percentage of aggregate, aggregate stability, organic materials, vkemntaoan C-organic content, volume weight, total pore space, aggregate percentage and aggregate stability and highest crop yield were found at a dose of 20 tons of mixture of cow manure and Tithonia Based on the organic bahab double rengri test, volume weight, total pore noise to the aggregation stability R 2 =.0.89.